An Evaluation of the ‘English for Nusantara’ Grade VII Textbook: Content, Language, and Design Aspects - Serli Ariska; Fitriyah; Cahaya Ningrum; Akhmad Ali Mirza (Journal Of Foreign Language Learning and Teaching, 2025)
This study aims to evaluate the English for Nusantara Grade VII textbook in terms of content, language, and layout design based on criteria proposed by Tomlinson (1998). Using a qualitative descriptive method, the textbook is analyzed according to five main aspects: physical appearance, structure and organization, activities, vocabulary and grammar, and language level. The evaluation shows that the textbook is visually appealing and appropriately structured for Grade VII students. The activities are varied and interactive, encouraging student participation. The vocabulary and grammar presented are suitable for the learners’ proficiency level, and the overall language use is accessible and appropriate. Based on these findings, the textbook is considered effective in supporting English language learning at the junior high school level.